Cross-hedging performance of wholesale beef in live cattle futures contracts revisited - Bieroth, Casey W. (Kansas State University, 2010)
Risk management decision makers face significant price risk when purchasing or selling wholesale beef. Previous research has identified cross-hedging wholesale beef in Live Cattle futures as a plausible means of reducing this risk. Changes in the way beef is marketed have led to poor performance of cross-hedging programs. Unlike earlier research, more recent studies have shown that Live Cattle futures are a poor venue for effective cross-hedging. This study replicates previous research to evaluate the current state of traditional cross-hedging performance. Focus then shifts to improving cross-hedging methods. Hedge ratios derived from a traditional cross-hedging methodology exhibit a great deal of sensitivity to season, estimation technique, and quality grade. Basis risk is abundant for this type of cross-hedging. To reduce the basis risk inherent with cross-hedging wholesale beef, bundling is proposed. This involves combining two or more cuts together in a single unit to be cross-hedged. Firms merchandising meat from a whole carcass would be able to provide a valuable risk management service if the basis risk faced when hedging a bundled product is less than the basis risk faced when cross-hedging the corresponding products independently. This research found that bundling has neither a positive or negative effect on basis risk. Therefore bundling is a plausible practice, but will not offer reduced basis risk to decision makers.
Keywords: Cross-Hedging; Beef Price Risk; Bundling; Economics, Agricultural (0503)